Sistem Check-In Di Lingkungan Sma Budya Wacana Dengan Memanfaatkan Qr Code Dan Geolokasi - Gozales, Ferdinand; Maria Nila Anggia Rini; Lukas Chrisantyo (Fakultas Teknologi Informasi, 2024)
Technology began to develop rapidly at that time. Many tools have been invented to facilitate human work, one of which is the Quick Response Code. QR Codes are two-dimensional matrix codes or barcodes created to allow scanners to respond quickly and receive data quickly. QR Codes can be used to manage the attendance of students, teachers, and school staff. This study defines a QR Code work system for student, teacher, and staff badges to manage student, teacher, and staff activity data and keep track of all students attending school. employee activities. This study uses the Waterfall System Development Life Cycle method. The key component of the system is a webcam scanner that reads QR Codes filled with master keys for student, teacher, and staff data. Attendance plays an important role in all institutions. This can lead to errors on the part of the school or students. For example, inefficient use of paper, absenteeism, missing monthly reports, missing wastepaper, etc. In addition, handwritten attendance carries the risk of absenteeism due to corruption of attendance data, which can lead to carelessness by employees and students.